Uncovering trauma in ukrainian war poetry translated into English - Жилко, Олександр Адамович (Волинський національний університет імені Лесі Українки, 2025)
This master’s thesis examines the process of translating contemporary Ukrainian war poetry into English as a psycholinguistic and discursive phenomenon. The research aims to identify and describe the psycholinguistic translation regularities that shape English translations of Ukrainian war poems, with particular attention to the transmission and transformation of trauma-related discourse features, coherence patterns, and emotional and cognitive structures. The study focuses on how normalisation, explicitation, equalisation and simplification appear in translation, integrating quantitative corpus analysis using LIWC2015 with qualitative linguostylistic examination of author-identified Markan Verses, the generative poetic lines that form the semantic and emotional nucleus of the poem.

Дипломна робота присвячена вивченню перекладу сучасної української воєнної поезії англійською мовою як психолінгвістичного та дискурсивного явища. Метою дослідження є виявлення і характеристика психолінгвістичних регулярностей перекладу, що визначають спосіб передачі травматичного дискурсу, когерентності та емоційно-когнітивних структур в англійських перекладах. Особлива увага приділяється тому, як нормалізація, експлікація, еквалізація та спрощення проявляються у перекладах на основі кількісного аналізу корпусу за допомогою LIWC2015 та якісного лінгвостилістичного аналізу маркових рядків — початкових поетичних імпульсів, що формують емоційне та смислове ядро тексту.
Keywords: trauma; war poetry; translation; psycholinguistic; regularities; Markan Verse; LIWC2015; poetic form